X-RAY-MORPHOLOGICAL PECULIARITIES OF THE LONG BONES AND RECONSTRACTION OF THEIR STRUCTURE AFTER ELIMINATION OF KNEE JOINT DEFORMATION IN CHILDREN WITH HEMATOGENOUS OSTEOMYELITIS CONSEQUENCES - Yu. M. Alexandrov; D. A. Alekberov; K. A. Diyachkov (Вестник хирургии имени И.И. Грекова)
Roentgeno-morphological peculiarities of the bones forming the knee joint were studied in 47 patients with knee deformation caused by hematogenous osteomyelitis before and after treatment by the method of transosseous osteosynthesis. The stages of reconstruction of distraction regenerate were observed by radiography and computed tomography methods.